1991
DOI: 10.1007/bf00176758
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin expression in the epithelia of the adult human cochlea

Abstract: Epithelia can be characterized by the specific expression pattern of their cytokeratin components. Therefore, we investigated the immunohistochemical expression of different cytokeratin subunits in frozen sections of chemically fixed, non-decalcified, adult human cochleas. The organ of Corti and the marginal cells of the stria vascularis showed reactivity for cytokeratin subunits 8, 18 and 19, whereas the other cochlear epithelia in addition expressed cytokeratin 7. The expression of cytokeratins 7, 8, 18 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Two separate antibodies to cytokeratins label the lumenal extensions of mature support cells in an increasing gradient from the cochlear base to its apex. A similar pattern of cytokeratin expression in support cells has been demonstrated in normal mammalian cochlea and vestibular organs (Raphael et al, 1987;Schrott et al, 1988;Anniko et al, 1989Anniko et al, , 1990Anniko and Arnold, 1990;Bauwens et al, 1991;Kuipers et al, 1991) but has not been reported previously in the chick inner ear. Cytokeratin labeling is pronounced in only a subset of support cells along the inferior, abneural edge of control basilar papillae.…”
Section: Cell-selective Markers In the Normal And Regenerating Cochlesupporting
confidence: 76%
See 2 more Smart Citations
“…Two separate antibodies to cytokeratins label the lumenal extensions of mature support cells in an increasing gradient from the cochlear base to its apex. A similar pattern of cytokeratin expression in support cells has been demonstrated in normal mammalian cochlea and vestibular organs (Raphael et al, 1987;Schrott et al, 1988;Anniko et al, 1989Anniko et al, , 1990Anniko and Arnold, 1990;Bauwens et al, 1991;Kuipers et al, 1991) but has not been reported previously in the chick inner ear. Cytokeratin labeling is pronounced in only a subset of support cells along the inferior, abneural edge of control basilar papillae.…”
Section: Cell-selective Markers In the Normal And Regenerating Cochlesupporting
confidence: 76%
“…We reacted whole mounts of the basilar papilla with antibodies to calmodulin, which have been shown to label hair cells selectively in the mature mammalian organ of Corti (Flock et al, 1986;Slepecky et al, 1988;Bauwens et al, 1991;Slepecky and Ulfendahl, 1993), and with the TUJ1 antibody, which labels class III ␤ tubulin in early differentiating neurons (Moody et al, 1989;Lee et al, 1990;Easter et al, 1993). In addition to examining the pattern of antibody labeling in the intact whole mounts, we embedded immunoreacted cochleae in plastic and sectioned them so that the cellular distribution of each antigen could be determined.…”
Section: Immunolabeling Of Hair Cells In Normal and Drugdamaged Cochlmentioning
confidence: 99%
See 1 more Smart Citation
“…The same CK subtypes have recently been demonstrated in the adult human cochlea. 16 However, in the adult human endolymphatic duct and sac, CKs typical of complex epithelia were found, since in this part of the inner ear the additional presence of CKs 14 and 17 was demonstrated." thelium of the vestibular labyrinth.…”
Section: Discussionmentioning
confidence: 98%
“…Antibodies to keratins 8, 18, and 19 bind to supporting cells in humans [Anniko et al, 1990;Bauwens et al, 1991a] and rats as well as guinea pigs [Kuipers et al, 1991]. This report provides evidence that deployment of these keratins in guinea pig supporting cells is spatially precise and nonuniform.…”
Section: Keratin Filament Deploymentmentioning
confidence: 50%